Association between non-hypervascular hypointense nodules on gadoxetic acid-enhanced MRI and liver stiffness or hepatocellular carcinoma. Issue 95 (October 2017) - Hwang, Jeong Ah; Kang, Tae Wook; Kim, Young Kon; Kim, Seong Hyun; Paik, Yong Han; Ha, Sang Yun; Kim, Seonwoo
Abstract: Purpose: To assess the association between non-hypervascular hypointense nodules (NHHNs) on gadoxetic acid-enhanced magnetic resonance imaging (MRI) and liver stiffness (LS) in patients with chronic liver disease, and analyzed their progression to overt hepatocellular carcinoma (HCC). Methods: Between August 2012 and March 2016, a total of 714 consecutive patients who had undergone transient elastography for LS measurement and gadoxetic acid-enhanced MRI were investigated. The association between the presence of NHHNs on the hepatobiliary phase and LS, and the patient's HCC status [none, presence of treatment-naïve HCC, or a history of previous HCC treatment] was assessed. In patients with these nodules, cumulative progression rates of nodules to overt HCC were compared with rates of new HCC development in other parts of the liver. Results: The prevalence of NHHNs was 16.8% (120/714). The presence of these nodules was significantly associated with the log LS (Odds ratio [OR], 1.48, p = 0.002) and hepatitis B virus infection (OR, 3.14, p = 0.017), regardless of the patient's HCC status. The two year cumulative progression rate of overt HCC from corresponding nodules and rate of progression to HCC in other parts of the liver were 34.1% and 18.3%, respectively ( p = 0.071). Conclusion: The presence of NHHNs on gadoxetic acid-enhanced MRI was associated with higher LS and hepatitis B virus infection. Furthermore, these lesions frequently progressed to overt HCC.